Konservasi Kotoran Sapi untuk Mendukung Desa Wisata - Dyah Pita Rengga, Wara; Wulansarie, Ria; Wijayatim, Nanik; Tunggul Pawenang, Eram (Universitas Negeri Semarang, 2019)
In Nongkosawit village, district Gunungpati, Semarang, the availability of livestock are very abundant in the presence of 60 cows. Cowshed has been allocated respectively integrated with cattle owners in accordance with its cows. The work program carried out by Tim IbM is the extension of energy conservation from cow manure into biogas energy and fertilizer plants, an environmental sanitation in the cowshed construction of biogas digester installation and provision of water pumps and packing of organic fertilizer in the tourist village. Biogas energy can be used for lighting and cooking while its by-products can be used as fertilizer. Gain on sale of fertilizers is four times the price than cow dung. The fertilizer contains elements N, P, and K atoms that can nourish plants in sufficient quantities.